2018
DOI: 10.1007/s12603-017-0947-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Activities of Daily Living Disability Situation and Association with Chronic Conditions among Elderly Aged 80 Years and Over in China

Abstract: The prevalence of ADL disability declined among the oldest-old population in China from the year of 1998 to 2008 without obeying a linear pattern. Temporal trends of ADL disability mainly attributed to the change of low disability level prevalence. Stroke/CVD and cognitive impairment were the most common risk factors of disability. Vision impairment caused disability has become less common, while risks of multimorbidity related disability increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…In a cross-sectional study including 567 participants 80 years and older multimorbidity was found to be associated with disability [42] but in a cohort study with 3 years follow-up time including the same participants multimorbidity predicted mortality and hospitalization but not functional decline [43]. A Chinese study including 52,667 participants over 80 years found that the association between multimorbidity and ADL disabilities became stronger between 1998 and 2008 [44]. Thus, the associations between multimorbidity and function may change over time and be different among the oldest old.…”
Section: Discussionmentioning
confidence: 96%
“…In a cross-sectional study including 567 participants 80 years and older multimorbidity was found to be associated with disability [42] but in a cohort study with 3 years follow-up time including the same participants multimorbidity predicted mortality and hospitalization but not functional decline [43]. A Chinese study including 52,667 participants over 80 years found that the association between multimorbidity and ADL disabilities became stronger between 1998 and 2008 [44]. Thus, the associations between multimorbidity and function may change over time and be different among the oldest old.…”
Section: Discussionmentioning
confidence: 96%
“…Their data quality has been verified in previous literatures [13,14,19,20]. These data had been widely used in the studies on elderly health in China [9][10][11]. The detailed information on the survey design is described in Additional file 1.…”
Section: Methods 21 Datamentioning
confidence: 78%
“…The index of independence in activities of daily living (ADL) developed by Katz and colleagues is one of the most widely used tool to serve this purpose [5][6][7][8]. The Chinese national surveys incorporating ADL and relevant literatures are more and more available in recent years [9][10][11][12][13][14]; however, the real level of physical disability among older people in China is still a myth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em comparação, as doenças cardíacas apresentavam chance de 1,55 vezes em 10 anos, aumentando a chance para 1,60 ao ajustar todas as outras condições mencionadas anteriormente 24 . Os achados da presente pesquisa, no entanto apontam que os sintomas provavelmente poderão ter uma associação preditiva mais importante do que simplesmente o diagnóstico.…”
Section: Discussionunclassified